INTEGRATED REPORTING ADOPTION: SUSTAINABLE CORPORATE STRATEGY IN ACHIEVING SDG 2030 - Belinda Azzahra (AJAR, 2022)
The environmental crisis has initiated companies to implement sustainability accounting as a business sustainability strategy. One indicator of this implementation based on POJK No 51/2017 is the availability of integrated reports (financial reports and sustainability reports) that can be accessed by the public. This paper aims to explain the essence of implementing sustainability strategy through adopting integrated reporting schemes in the company. Therefore, the company does not only implement it to the extent of fulfilling the demands of the government, but for the benefit of the company in the long term. The author uses a quantitative and qualitative analysis approach with the variable earnings per share and the growth of the company's stock price in the sector of financial services institutions and public companies. Furthermore, the author also analyses the fundamental weakness of the integrated reporting systematics which makes it difficult to compare between companies. This paper offers a universal measurement standard that can be used by external and internal parties of the company in assessing how far the company is implementing its sustainability strategy through creating integrated reports. This standard will prove the company's ability to maintain its business continuity in the long term and affect its current valuation. However, it cannot be denied that the sustainability strategy launched by the Indonesian government still has several weaknesses. Therefore, this paper also answer the challenges of the role of accountants in Indonesia in implement sustainability accounting, especially in adopting integrated reporting scheme.